2021
DOI: 10.1111/iej.13569
|View full text |Cite
|
Sign up to set email alerts
|

Influence of metal artefact reduction tool on the detection of vertical root fractures involving teeth with intracanal materials in cone beam computed tomography images: A systematic review and meta‐analysis

Abstract: Background The effectiveness of the metal artefact reduction (MAR) tool for the detection of vertical root fracture (VRF) by cone beam computed tomography (CBCT) images is controversial. Objective To evaluate the effectiveness of the MAR tool on VRF detection involving teeth with intracanal materials in CBCT images. Methodology In September 2019, an electronic search was performed in six databases (PubMed, Scopus, Web of Science, Cochrane, Lilacs and Embase). The electronic search was updated in May 2020 throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
(105 reference statements)
0
9
1
1
Order By: Relevance
“…The highest sensitivity (100%) were for scan group without implant with which denotes that CBCT images are highly accurate in vertical root fracture detection and diagnosis when metal artifacts are not present. (20,29,30,(32)(33)(34)(35)37,38) The sensitivity level for scan group with implant without AR was 96.7%. The decrease in sensitivity means that metal artifact could obscure the fracture line in CBCT image giving false negative results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest sensitivity (100%) were for scan group without implant with which denotes that CBCT images are highly accurate in vertical root fracture detection and diagnosis when metal artifacts are not present. (20,29,30,(32)(33)(34)(35)37,38) The sensitivity level for scan group with implant without AR was 96.7%. The decrease in sensitivity means that metal artifact could obscure the fracture line in CBCT image giving false negative results.…”
Section: Discussionmentioning
confidence: 99%
“…The highest specificity levels were reported for group without implant (100.0%) highlighting the high validity and diagnostic ability of CBCT in detection of vertical root fracture as reported in many studies to be attributed to the parameter's selection and the homogeneity of the study samples. (20,30,32,35,38) However, results by Dias et al (23) disagree as they reported poor specificity for CBCT in vertical root fracture with or without metal artifact presence. Specificity for group with implant without AR was 90.0%.…”
Section: Discussionmentioning
confidence: 99%
“…The application of these strategies has been examined, but the ndings have been uneven. Fontenele et al [45] found that the MAR tool has a negative effect on the diagnostic accuracy of vertical root fracture in the presence of intracanal lling. Also, Kamburoglu et al…”
Section: Discussionmentioning
confidence: 99%
“…The application of these strategies has been examined, but the findings have been uneven. Fontenele et al [ 46 ] found that the MAR tool has a negative effect on the diagnostic accuracy of vertical root fracture in the presence of intracanal filling. Also, Kamburoglu et al [ 47 ] evaluated the effects of four MAR protocols (off, low, medium, and high) for the assessment of periodontal and peri-implant defects, and they found no difference in diagnostic accuracy with any MAR protocol.…”
Section: Discussionmentioning
confidence: 99%